METODE AMTSAL FIL QUR’AN PADA PENDIDIKAN AKIDAH ANAK: URGENSI DAN PENERAPANNYA PADA QS. IBRĀHĪM: 24-25 - Sinta Hardiyanti Utami; Vida Ravida (LPPM IAD Probolinggo, 2025)
Children’s faith education is a fundamental element in shaping character and belief. However, the abstract nature of aqidah concepts often poses challenges in the learning process. This study aims to analyze the urgency and application of the Amtsal fil Qur’an method as an effective approach in teaching aqidah to children, with a specific focus on Surah Ibrahim: 24–25. This approach offers a way to translate abstract values into concrete visualizations that are easier for children to understand. The study uses a descriptive-analytical method with a qualitative approach. The findings show that the use of Amsal, such as the parable of the kalimah tayyibah likened to a good tree, provides a powerful illustration of strong faith, ongoing good deeds, and noble character. The study concludes that Amtsal fil Qur’an is a relevant and effective method for teaching aqidah to children. Despite some challenges in its implementation, this approach holds great potential in shaping a generation with firm belief and good character. This research offers a valuable contribution to the development of Islamic teaching methods, particularly in aqidah education, and is expected to serve as a useful reference for educators. Keywords: Amtsal fil Qur’an; Children; the Education of Aqeedah